2021
DOI: 10.1113/ep089547
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 accelerates renal tubular epithelial cell damage by modulating mitophagy via miR‐150‐5p–DRP1 axis in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a severe complication in diabetic patients, with a high mortality rate. Renal tubular injury is involved in the pathogenesis of DN. In this study, we aimed to uncover the regulatory roles of the NEAT1-miR-150-5p-DRP1 axis in an in vitro model of DN and its possible mechanisms. High glucose-challenged HK-2 cells were used as an in vitro DN model. NEAT1, miR-150-5p and DRP1 levels were assessed by RT-qPCR. Cell viability was determined by the MTT assay. MitoSOX Red and JC-1 were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…As a structural component of nuclear paraspeckles [ 27 ], it binds RNAs causing their nuclear retention, which prevents their export to the cytoplasm and thus their translation [ 37 ]. NEAT1 modulates gene expression by sponging numerous miRNAs [ 28 , 29 , 30 , 31 , 38 ]. The exact mechanism needs to be elucidated since NEAT1 localizes to the nucleus while miRNAs have their place of action in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a structural component of nuclear paraspeckles [ 27 ], it binds RNAs causing their nuclear retention, which prevents their export to the cytoplasm and thus their translation [ 37 ]. NEAT1 modulates gene expression by sponging numerous miRNAs [ 28 , 29 , 30 , 31 , 38 ]. The exact mechanism needs to be elucidated since NEAT1 localizes to the nucleus while miRNAs have their place of action in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to DKD, others showed a positive and negative correlation, respectively, between elevated urinary NEAT1 and various podocyte damage markers like synaptopodin and podocalyxin or GFR [ 42 ]. HG-exposed proximal tubular cells (HK-2) or murine MCs (mMCs) exhibited an increase in NEAT1 expression in a dose- or time- dependent manner [ 31 , 43 ]. Contrarily to others, our data indicate that NEAT1 expression is not affected by HG using an osmotic control and a species model, in which NEAT1 is annotated (human or murine) [ 31 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study has revealed that lncRNA SNHG14 (small nucleolar RNA host gene 14), activates mitophagy by upregulating the expression of BNIP3, Beclin-1 and LC3II/LC3I ratio ( Deng et al, 2020 ). Also, the findings of a recent study uncovered that the lncRNA NEAT1(nuclear paraspeckle assembly transcript 1)- miR-150-5p-DRP1 axis regulates mitophagy ( Yang et al, 2021 ). There are several studies published in recent years confirming epigenetic regulation of mitophagy.…”
Section: Introductionmentioning
confidence: 99%